Nagari Minangkabau: Studi terhadap Kelembagaan Masyarakat Adat di Sumatera Barat, Indonesia - Azwar, Welhendri; Yunus, Yulizal; Muliono, Muliono; Permatasari, Yuli (Jurnal Bina Praja, 2018)
Nagari as government and customary institutions in West Sumatra is torn between the interests of the government system and the importance of maintaining the fundamental values in the community. Various government regulations regarding the village or Nagari generate new questions, the loss of the communityâ€™s identity and local wisdom of Nagari as an autonomous and independent society. This study aims to explore and describe the Nagari system of government, as a social system of indigenous peoples of Minangkabau that combine the state government system with the adat system of local customary institutions. The study was conducted with qualitative methods, using in-depth interviews with the community leaders as well as some observations related to the dynamics of its social community in addition to literature study. This study found that Nagari as Minangkabau community social unity has a sacred local wisdom from the communityâ€™s comprehensive thinking, and natural conditions. With its history, Nagari grows as an autonomous region where the community manages the social and natural resources potential independently. The Institutional system of Nagari is a combination between the state, custom, and religion, which is combined in the framework of tungku tigo sajarangan, tali tigo sapilin, the government, niniek mamak, and religious scholars. The social system that emerged from the wisdom of â€œreadingâ€ nature, as the strength of the Minangkabau community, made Nagari be one of the regions in Indonesia which are called by the Netherlands as â€œthe Small Republicâ€.